1996
DOI: 10.1080/00071669608417864
|View full text |Cite
|
Sign up to set email alerts
|

Line differences in resistance tosalmonella enteritidispt4 infection

Abstract: 1. Four groups of hens, each of a different line, were inoculated at peak of lay, per os in the crop with 1 ml of a suspension containing 10(9) cfu/ml Salmonella enteritidis PT4 (SE). The kinetics of SE contamination in the environment, egg shell and yolk were studied during the first 28 d post inoculation. On the day of slaughter, intestines, caeca, spleen, liver, ovary, oviduct and content were investigated for SE contamination. 2. The commercial egg-type line L2 was found to be the most susceptible to SE. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Indeed, Protais et al [9] observed large differences when comparing poultry lines inoculated at the same time and with the same dose of inoculation. The model derived by Prévost et al [7] may be used for such data: since each line was reared separately, it was possible to process one subpopulation at a time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, Protais et al [9] observed large differences when comparing poultry lines inoculated at the same time and with the same dose of inoculation. The model derived by Prévost et al [7] may be used for such data: since each line was reared separately, it was possible to process one subpopulation at a time.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is partially under genetic control. Such a result could be expected from the large difference in kinetics of bacterial clearance between poultry lines [9]. The L2 egg-type line, in particular, was found to be susceptible to the Salmonella carrier-state, whether in the digestive tractus, the systemic organs or the ovaries.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations